2009
DOI: 10.1007/s00420-009-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

Validity of new biomarkers of internal dose for use in the biological monitoring of occupational and environmental exposure to low concentrations of benzene and toluene

Abstract: Our research confirmed the validity of t,t-MA and SPMA for use in the biological monitoring of exposure to low concentrations of benzene. Urinary benzene showed comparable validity to SPMA; both parameters are affected by smoking cigarettes in the hours before urine collection, so it is best to ask subjects to refrain from smoking for 2 h before urine collection. Urinary toluene was found to be a more specific biomarker than SBMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 66 publications
3
34
0
4
Order By: Relevance
“…BEN-A levels were similar to those measured in petrol station attendants from Milan in the year 2000 (Fustinoni et al, 2005), but were more than twice than those reported in other Italian cities in the same year (Ghittori et al., 2010;De Palma et al, 2012). Higher values are likely because of the higher volume of fuel dispensed in the area of Milan (>850 000 tons of petrol in 2007), relative to the smaller Italian cities investigated (<200 000 tons in 2007) (Ministero Sviluppo Economico, 2007).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…BEN-A levels were similar to those measured in petrol station attendants from Milan in the year 2000 (Fustinoni et al, 2005), but were more than twice than those reported in other Italian cities in the same year (Ghittori et al., 2010;De Palma et al, 2012). Higher values are likely because of the higher volume of fuel dispensed in the area of Milan (>850 000 tons of petrol in 2007), relative to the smaller Italian cities investigated (<200 000 tons in 2007) (Ministero Sviluppo Economico, 2007).…”
Section: Discussionsupporting
confidence: 53%
“…The difference is due to the use, in the present study, of a specific and sensitive method based on LC-MS-MS, while the previous study utilized an immunoassay kit. Other studies provide supporting evidence for this conclusion (Lovreglio et al 2010;De Palma et al, 2012), and also support the need for ongoing development of new methods for this analysis (Fustinoni et al, 2010b(Fustinoni et al, , 2011.…”
Section: Discussionmentioning
confidence: 93%
“…Biomarker sebagai indikator biokimia dapat diaplikasikan untuk melihat kerusakan lingkungan dengan mengukur paparan polusi pada manusia (Roosmini et al, 2006) Biomarker yang dapat digunakan untuk monitoring biologi paparan benzene antara lain t,t-muconic acid, S-phenylmercapturic acid (SPMA), dan fenol (Lovreglio, 2010). Menurut Hoet (2009), SPMA dan urinary benzene memiliki akurasi yang sama.…”
Section: Metodologiunclassified
“…Although phenol and its conjugates are the more abundant biotransformation products for benzene, these compounds are not suitable as specific biomarkers for benzene as they can also be the metabolic products of other common chemicals. As with BMA from its parent toluene, PMA is the preferred metabolite for use as biomarker for benzene exposure (Lovreglio et al 2010;Melikian et al 1999) and is the target for the current study.The compound 2-(2-methoxyethoxy) ethanol (also known as diethylene glycol monomethyl ether [DiEGME] and under the trade name of methyl carbitol, CAS 111-77-3) is another component of JP-8. It is unique in being an additive in the formulation of JP-8 for the military and is at a consistent concentration of 0.1% (v/v) for every batch of the fuel as previously described.…”
mentioning
confidence: 99%
“…Although phenol and its conjugates are the more abundant biotransformation products for benzene, these compounds are not suitable as specific biomarkers for benzene as they can also be the metabolic products of other common chemicals. As with BMA from its parent toluene, PMA is the preferred metabolite for use as biomarker for benzene exposure (Lovreglio et al 2010;Melikian et al 1999) and is the target for the current study.…”
mentioning
confidence: 99%